Distribuição temporal e espacial da Leishmaniose visceral em humanos e cães em Belo Horizonte-MG, 1993 a 2007. - Eliane Goncalves Paiva Lopes (2009)
The aim of this study was to describe the chronological series analysis and determine the tendency of both human and canine visceral leshmaniasis in Belo Horizonte city, including its nine setors of public health, from 1993 to 2007. From 1994, when the first cases of the disease were reported, until 2007, 994 human cases were recorded, which led to 116 deaths. From 1993 to 2007, 1,492,401 samples of canine blood were analyzed at the Laboratório de Zoonoses da Secretaria Municipal de Saúde de Belo Horizonte (LZOON/SMSA-PBH), by the Enzyme-Linked Immunosorbent Assay (ELISA) as screening test and by the Indirect Immunofluorescence Reaction (RIFI) as confirmatory test. The rate of positive results was 5.93%. Dividing the chronological series of the study in two periods (from the onset of the cases to 2000 and from 2001 to 2007), it was observed that in the latter, there was a tendency of increasing the coefficient of incidence in humans and prevalence in dogs, and opposite results were verified in the first period. Canine visceral leishmaniasis did not show a regional distribution, which requires that permanent control actions be adopted throughout the year and it was not possible to determine whether the phenomenon was cyclic or not. Human and canine visceral leishmaniasis showed a broad spatial distribution in the nine administrative sectors which a differentiated risk of illness, in spite of the presence either of the sources of infection or the susceptible individuals in the whole county